Cisplatin-resistant bladder carcinoma cells: enhanced expression of metallothioneins - Siegsmund, Michael; Marx, Claudia Christine; Seemann, Othmar; Schummer, Bernhard; Steidler, Annette; Toktomambetova, Lira; Köhrmann, Kai-Uwe; Rassweiler, Jens; Alken, Peter (Urological research, 1999)
Cisplatin is one of the most potent cytotoxic drugs and in chemotherapy has ameliorated numerous tumors. Nevertheless, resistance to cisplatin is a problem that is encountered in the chemotherapy of urologic tumors, especially transitional cell carcinomas. In order to improve definition of the mechanisms of cisplatin-resistance we established a series of cisplatin-resistant sublines from the cell line RT 112 in increasing concentrations of cisplatin. The most resistant subline CP3 is approximately 10 times more resistant than the parental line and shows a 10-fold cross-resistance against methotrexate, whereas vinblastine and doxorubicin are equally effective in the parental and sublines. Combined treatment of CP3 cells with cisplatin and buthionine sulfoximine (BSO) does not result in enhanced cell kill, thereby ruling out glutathione as a resistance mechanism. However, in comparison with parental cells, CP3 cells are about 1.5 times more resistant against cadmium. On the protein level, the cisplatin-resistant cells reveal an enhanced expression of metallothionein II (MTII), but not MTI, suggesting that the cisplatin resistance we observed in these sublines is at least partly mediated by MTII. These sublines will in the future serve as valuable tools for the analysis of cisplatin resistance, especially in view of metallothionein-mediated resistance mechanisms.